Pendekatan Violin Plot sebagai Pengenalan Pola untuk Interpretasi Data Penjualan Spare Part Komputer - Furqoni Yudhistira; Erlin Windia Ambarsari; Frieyadie (Journal of Informatics, Electrical and Electronics Engineering, 2023)
This study examines the use of visual modeling in understanding the sales patterns of computer spare parts at PT Prima Krida Solusindo. The use of violin plots serves as a method for data interpretation, focusing on the distribution of sales data to gain a deeper understanding of customer needs. This study involves 3893 samples with eight features being analyzed. Initial results show a broad variation in the sales of computer spare parts. For example, the highest unit sales occur in the first quarter, but the sales volume tends to be low. Opposite, sales in the second quarter tend to focus on purchases with a relatively similar volume. In addition, preferences for distribution channels, sales segmentation, sub-segmentation, and product types also vary in sales volume. While the violin plot aids in visualizing data distribution, this study also found that this method has limitations, such as category overlapping, that complicate interpretation. The inclusion of additional plots can facilitate a more detailed interpretation